Knockdown of hnRNPA1 Promotes NSCLC Metastasis and EMT by Regulating Alternative Splicing of LAS1L exon 9 - Han, Peng; Cao, Peng; Yue, Jiaqi; Kong, Kangle; Hu, Shan; Deng, Yu; Li, Lequn; Li, Fan; Zhao, Bo (Frontiers in Oncology, 2022)
Tumor metastasis is still an insurmountable obstacle in tumor treatment. Lung cancer represents one of the most common malignancies with high morbidity worldwide. hnRNPA1 has been reported to be involved in the regulation of tumor metastasis, while its specific role in tumor metastasis seems to be controversial and its molecular mechanism in lung cancer metastasis remains to be further elucidated. In this study, we confirmed that knockdown of the hnRNPA1 led to enhanced migration, invasion and EMT transition in lung cancer cells. Bioinformatics analysis of the GSE34992 dataset revealed that hnRNPA1 may regulate the alternative splicing (AS) of LAS1L exon 9. Further AGE assays and RIP assays revealed that hnRNPA1 can directly bind to the LAS1L pre-mRNA to inhibit the splicing of LAS1L exon 9. The RNA pull-down assays showed that hnRNPA1 can specifically bind to the two sites (UAGGGU(WT1) and UGGGGU(WT3)) of LAS1L Intron 9. Further Transwell assays indicated that the expression ratio of LAS1L-L/LAS1L-S regulated by hnRNPA1 can further promote the migration, invasion and EMT transition in lung cancer cells. Moreover, hnRNPA1 expression showed significant heterogeneity in lung cancer tissues, which may contain new research directions and potential therapeutic targets. Our results indicate that hnRNPA1 can affect the metastasis of lung cancer cells by modulating the AS of LAS1L exon 9, highlighting the potential significance of hnRNPA1 in lung cancer metastasis.